Two-Center Experience in the Endovascular Treatment of Intracranial Aneurysms Using the Woven EndoBridge 17 Device Including Midterm Follow-Up Results: A Retrospective Analysis - Maurer, C.; König, I.; Berlis, A.; Weber, W.; Fischer, S. (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: The Woven EndoBridge device proved its effectiveness in the treatment of ruptured and unruptured intracranial aneurysms as a stand-alone device. Before 2016, Woven EndoBridge deployment required at least a 0.021-inch microcatheter. In 2016, a smaller device, the Woven EndoBridge 17 with finer size increments that used a 0.017-inch microcatheter, was introduced. We retrospectively analyzed our initial and follow-up results with the Woven EndoBridge 17 in ruptured and unruptured aneurysms.MATERIALS AND METHODS: One hundred twenty-seven intracranial aneurysms in 117 patients were scheduled for treatment with the Woven EndoBridge 17 between June 2017 and February 2019. Twenty-nine aneurysms were ruptured.RESULTS: Treatment was performed as intended in 124 of 127 cases (97.6%). Additional devices such as stents or coils were used in 12 cases (9.7%). Five thromboembolic complications and 1 hemorrhagic complication were encountered, resulting in clinical deterioration in 2 patients. The overall morbidity and mortality in the entire series have been 1.7% and 0.0% to date, respectively. The follow-up results at 3 and 12 months revealed complete occlusion in 76.1% (70/92) and 78.0% (32/41).CONCLUSIONS: The Woven EndoBridge 17 device is safe in the treatment of small broad-based aneurysms without the general need for additional devices. The low complication rate and the promising follow-up results underline the value of this technique in a growing range of endovascular treatment options for intracranial aneurysms.AcomAanterior communicating arteryGCPgood clinical practice